Foreign policy, domestic politics and international relations : the case of Italy - Brighi, Elisabetta (London ; Routledge, Taylor & Francis Group, 2013)
"This book offers a re-examination of foreign policy, in its relation with domestic politics and international relations"--
Includes bibliographical references (pages 166-189) and index.
Keywords: POLITICAL SCIENCE / General; Italy -- Foreign relations -- 1994-; Italy -- Politics and government -- 1994-2018.